P57 Soluble receptor for advanced glycation end-products (srage) in patients with copd: the erica study. (15th November 2017) - Siraj, R; McKeever, TM; Buss, L; Mohan, D; Maki-Petaja, K; Forman, J; McEniery, CM; Cheryian, J; Gale, N; Cockcroft, JR; Calverley, PM; MacNee, W; et al.
Abstract : Background: Advanced glycation endproducts (AGE) in patients with chronic obstructive pulmonary disease (COPD) has been considered in the pathology of the disease and as a biomarker of emphysema severity. In addition, AGE has been implicated in cardiovascular (CV) disease, a common comorbidity in COPD. Whether the soluble receptor for AGE (sRAGE) predicts CV status in COPD is unclear. Objective: The aim of this study was to assess the associations between sRAGE and measures of both lung and CV function in patients with COPD from the ERICA cohort. Methods: Patients with confirmed COPD performed spirometry, blood pressure, aortic pulse wave velocity (PWV), carotid intima media thickness (CIMT) at clinical stability. Blood for sRAGE was taken. Results: Of the 729 subjects in ERICA, 677 patients had a sRAGE result. 417 patients were male; mean (SD) age was 67.4 (7.8) years and 31% were current smokers. There was a weak association of sRAGE with age (r=0.16, p<0.001), FEV1 % predicted (r=0.12, p<0.05) and FEV1/FVC (r=0.15, p<0.001). There was no difference in sRAGE in current or ex-smokers. In multiple linear regression, a lower sRAGE was associated with more severe lung function: FEV1 % predicted, (B 4.3 [95% CI 1.6, 6.8, p=0.0012]. No significant relationship was observed between sRAGE and cardiovascular variables: aortic PWV (p=0.418) and CIMT (p=0.596) in the multivariate models. sRAGE in those with concurrent presence of CV disease, diabetes or cerebrovascular disease or not was not different (p=0.579). Conclusion: Despite literature supporting the role of AGE in both lung and CV disease, there was no apparent association of sRAGE with CV status in patients with COPD in the ERICA cohort. There were associations with spirometry variables of FEV1% predicted and FEV1/FVC.